2019
DOI: 10.1158/1535-7163.mct-18-0953
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Therapeutic Efficacy of Oncolytic Herpes Simplex Virus-1 with Integrin β1 Blocking Antibody OS2966

Abstract: Integrin b1 receptor, expressed on the surface of tumor cells and macrophages in the tumor microenvironment (TME), has been implicated in both tumor progression and resistance to multiple modalities of therapy. OS2966 is the first clinical-ready humanized monoclonal antibody to block integrin b1 and was recently orphan designated by the FDA Office of Orphan Products Development. Here, we tested therapeutic potential of OS2966-mediated integrin b1 blockade to enhance the efficacy of oncolytic herpes simplex vir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“… 145 Blockade of ITGB1 with OS2966 (a humanized CD29 blocking antibody) overturned bevacizumab-induced resistance. 145 Although OS2966 enhanced oHSV replication and GBM cell cytotoxicity in vitro, 146 systemic OS2966 delivery did not enhance the anti-tumor efficacy of oHSV (rHSVQ1-IE4/5-Luciferase) in vivo. Insufficient delivery of OS2966 to the brain may have contributed to the failure to obtain a combination effect.…”
Section: Ohsv-based Combination Therapies For Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“… 145 Blockade of ITGB1 with OS2966 (a humanized CD29 blocking antibody) overturned bevacizumab-induced resistance. 145 Although OS2966 enhanced oHSV replication and GBM cell cytotoxicity in vitro, 146 systemic OS2966 delivery did not enhance the anti-tumor efficacy of oHSV (rHSVQ1-IE4/5-Luciferase) in vivo. Insufficient delivery of OS2966 to the brain may have contributed to the failure to obtain a combination effect.…”
Section: Ohsv-based Combination Therapies For Gbmmentioning
confidence: 99%
“…To overcome this issue, OS2966 was directly injected intracranially into GBM xenograft 2 days prior to oHSV treatment, and this time, the combination significantly extended survival compared to monotherapies. 146 In contrast to OS2966, systemic delivery of cilengitide (another integrin inhibitor) significantly enhanced the anti-glioma efficacy of RAMBO compared to single treatments. 147 Cilengitide has been evaluated in GBM patients 148 and could be a better choice than OS2966 for combination studies.…”
Section: Ohsv-based Combination Therapies For Gbmmentioning
confidence: 99%
“…Integrin-mediated entry has also been utilized to improve both viral tropism and replication [ 93 , 94 ]. Lee et al showed that the β1 integrin blockade improved replication of an HSV variant and promoted antitumor efficacy in patient-derived primary glioblastoma-bearing mice [ 95 ].…”
Section: Summary Of Preclinical Experiences With Combinatory Virotmentioning
confidence: 99%
“…Oncolytic viruses (OV) transform immunotherapy from a sterile immunity to a pathogen-associated-like immunity, as these viruses replicate preferentially in tumor cells and release TAAs and PAMPS [ 132 , 133 ]. In this emerging in situ vaccination strategy in breast cancer models, pox- [ 134 , 135 ], reo- [ 136 ], herpes simplex [ 137 , 138 , 139 ], adeno- [ 140 , 141 , 142 , 143 ], Newcastle disease [ 144 , 145 ], Vesicular stomatitis [ 146 ], and measles [ 147 , 148 , 149 ] viruses have been employed to make breast tumors more immunogenic and more responsive to immunotherapies by priming the TME to signs of infection and releasing TAAs [ 150 ]. Moreover, these viruses can be engineered to express various TAAs to further prime an immunological response from TME.…”
Section: Oncolytic Virusesmentioning
confidence: 99%